Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-10-11T18:59:06+02:00
F(x)=x³-2x²-3x+6 Miejsce zerowe to taki argument dla którego f(x)=0 zatem
f(x)=x³-2x²-3x+6=0
x³-2x²-3x+6=0
x²(x-2)-3(x-2)=0
(x²-3)(x-2)=0
(x-√3)(x+√3)(x-2)=0
x-√3=0 lub x+√3=0 lub x-2=0
x=√3 lub x=-√3 lub x=2
Odp. Miejscami zerowymi tej funkcji są x=√3 lub x=-√3 lub x=2.
2009-10-11T19:03:33+02:00
F(x)=x³-2x²-3x+6 =x²(x-2)-3(x-2)=(x-2)(x²-3)
0=(x-2)(x²-3)
x=2 lub x=-√3 lub x=√3
2009-10-11T19:09:04+02:00
F(x)=x³-2x²-3x+6


f(x)=x³-2x²-3x+6 = x²(x - 2) -3(x - 2) = (x - 2)(x² - 3) =
(x - 2)(x - √3)(x + √3)

miejsca zerowe:
-2; -√3;√3